Genetic resistance against helminth infections in cattle, sheep and goats in the tropics - Baker, R.L. (Utrecht University, 1995)
The paper reviews the limited data available on both between-and within-breed genetic variation for resistance to helminthiasis in cattle, sheep and goats in the tropics. Topics covered include criteria of resistance, resilience or tolerance, parasite species and mode of infection, parameters to be measured, and genetic variation for disease resistance.